Видатна дослідниця «чужинців» української флори - Бойко, М.Ф.; Ходосовцев, О.Є.; Мойсієнко, І.І.; Мельник, Р.П.; Багрікова, Н.О. (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Видатна дослідниця «чужинців» української флори